Vaccination with the Crimean-Congo hemorrhagic fever virus viral replicon vaccine induces NP-based T-cell activation and antibodies possessing Fc-mediated effector functions - Scholte, F. E. M.; Karaaslan, E.; O’Neal, T. J.; Sorvillo, T. E.; Genzer, S. C.; Welch, S. R.; Coleman-McCray, J. D.; Spengler, J. R.; Kainulainen, M. H.; Montgomery, J. M.; Pegan, S. D.; Bergeron, E.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Crimean-Congo hemorrhagic fever virus (CCHFV; family Nairoviridae) is a tick-borne pathogen that frequently causes lethal disease in humans. CCHFV has a wide geographic distribution, and cases have been reported in Africa, Asia, the Middle East, and Europe. Availability of a safe and efficacious vaccine is critical for restricting outbreaks and preventing disease in endemic countries. We previously developed a virus-like replicon particle (VRP) vaccine that provides complete protection against homologous and heterologous lethal CCHFV challenge in mice after a single dose. However, the immune responses induced by this vaccine are not well characterized, and correlates of protection remain unknown.Here we comprehensively characterized the kinetics of cell-mediated and humoral immune responses in VRP-vaccinated mice, and demonstrate that they predominantly target the nucleoprotein (NP). NP antibodies are not associated with protection through neutralizing activity, but VRP vaccination results in NP antibodies possessing Fc-mediated antibody effector functions, like complement activation (ADCD) and antibody-mediated cellular phagocytosis (ADCP). This suggests that Fc-mediated effector functions may contribute to this vaccine's efficacy.